Prevalence of adult smokers in Brazilian capitals according to socioeconomic deprivation - Regina Tomie Ivata Bernal; Deborah Carvalho Malta; Renato Azeredo Teixeira; Alastair Hay Leyland; Vittal Srinivasa Katikireddi; Elizabeth Bailey Brickley; Elzo Pereira Pinto Júnior; Maria Yuri Travassos Ichiara; Mirjam Allik; Ruth Dundas; Mauricio Lima Barreto (Revista Brasileira de Epidemiologia, 2023)
ABSTRACT Objective: To estimate the prevalence of adult smokers in the 26 capitals and the Federal District according to the Brazilian Deprivation Index (Índice Brasileiro de Privação – IBP). Methods: Dataset on smoking were obtained from the Surveillance of Risk and Protective Factors for Noncommunicable Diseases by Survey (Vigitel) system for the 26 capitals and the Federal District, in the period from 2010 to 2013. The IBP classifies the census sectors according to indicators such as: income less than ½ minimum wage, illiterate population and without sanitary sewage. In the North and Northeast regions, the census sectors were grouped into four categories (low, medium, high and very high deprivation) and in the South, Southeast and Midwest regions into three (low, medium and high deprivation). Prevalence estimates of adult smokers were obtained using the indirect estimation method in small areas. To calculate the prevalence ratios, Poisson models are used. Results: The positive association between prevalence and deprivation of census sector categories was found in 16 (59.3%) of the 27 cities. In nine (33.3%) cities, the sectors with the greatest deprivation had a higher prevalence of smokers when compared to those with the least deprivation, and in two (7.4%) there were no differences. In Aracaju, Belém, Fortaleza, João Pessoa, Macapá and Salvador, the prevalence of adult smokers was three times higher in the group of sectors with greater deprivation compared to those with less deprivation. Conclusion: Sectors with greater social deprivation had a higher prevalence of smoking, compared with less deprivation, pointing to social inequalities.